The relationship between audit quality and accounting conservatism in the Iraqi banks - Hassnain Raghib Talab, Ali Mohammed Thijeel, Hakeem Hammood Flayyih, (Opción, 2019)
The main objective of this study is to study and measure both concepts and the impact of audit quality on the accounting conservatism. The study employed both the SPSS and STATA as tools of analysis techniques to achieve reliable results. From the number of conclusions of the study, the most important of them is that the sample selected is of high quality, but did not limit the practice of accounting conservatism, although the financial statements of the Iraqi banks listed in the Iraqi Stock Exchange (ISX).